Isolated distal deep vein thrombosis: what we know and what we are doing - PALARETI, G.; SCHELLONG, S. (Journal of thrombosis and haemostasis, 2012)
Thromboses that are restricted to the infra‐popliteal deep veins of the lower limbs (isolated distal deep vein thrombosis, IDDVT) are frequently diagnosed in subjects with suspected pulmonary embolism (PE; 7–10%) or DVT (4–15%), accounting for 31–56% of all diagnosed leg DVTs. Despite their frequency, IDDVTs still remain one of the most debated issues in the field of venous thromboembolism (VTE). Conflicting clinical results have resulted in differing opinions on the need to test for IDDVTs and how to treat them. Due to discordant results, the real risk of IDDVT‐associated PE is not well established. IDDVTs are associated with (i) lower risk of recurrence when compared with other VTEs, and (ii) fewer late sequelae than proximal DVT. Diagnosis of IDDVT is based on ultrasound examination of all calf veins, which is more operator‐dependent and less sensitive than proximal vein examination. A series of studies has shown, however, that a single complete ultrasound strategy in symptomatic patients has comparable clinical results to serial proximal ultrasound, allowing approximately 15% better DVT diagnosis. Optimal treatment of IDDVT is still controversial. Guidelines recommend anticoagulation for 12 weeks, although 6 weeks may be sufficient. There is, however, insufficient data to support the diagnosis and treatment of all IDDVTs, and the necessary criteria to identify subjects at higher risk of complication are lacking. It also seems likely that different approaches may be better for unprovoked or secondary events and for deep or muscle veins. Specifically designed and adequately powered clinical studies addressing the issue of IDDVT need to be urgently undertaken.